Hegemony and Resistance in The Hunger Games (2012): A Gramscian Discourse Analysis - Nadine Zhafiira; Suardi Suardi (Magister Program of English Education, Fakultas Keguruan dan Ilmu Pendidikan Universitas Mulawarman, 2025)
This study investigated the representation of social position and hegemonic practices in The Hunger Games (2012) movie. The analysis focused on how the Capitol was portrayed as the ruling class and District 12 as the subaltern class, as well as how resistance emerged through counter-hegemonic actions. The study applied Antonio Gramsci’s concept of hegemony as the analytical framework and used a qualitative descriptive method to examine the characters’ dialogues. A total of 55 data points were identified, consisting of 13 related to social position, 38 representing different practices of hegemony, and 4 reflecting counter-hegemonic resistance. The findings revealed that the Capitol sustained dominance not only through political and economic control but also through cultural, ideological, and symbolic practices. At the same time, the acts of resistance performed by Katniss Everdeen demonstrated the possibility of class awareness and a challenge to hegemonic power. Beyond its theoretical contribution, this study also offered practical implications for English language teaching. Film dialogues from The Hunger Games could be used as authentic classroom materials to develop students’ critical literacy, encourage awareness of power relations in discourse, and promote reflective engagement with media texts. This highlighted the relevance of discourse analysis and critical pedagogy in fostering socio-political awareness among EFL learners.